A survey of mineral status of soils, feeds and cattle in the Selale Ethiopian highlands. II. Trace elements - Khalili, M.; Lindgren, E.; Varvikko, T. (Springer, 1993)
The trace element status of crossbred Friesian X Zebu (Boran) and local Zebu cattle in the Selale highlands of Ethiopia was evaluated during the rainy and dry seasons of 1989 and 1990 interms of the trace element content of soils, feeds, blood plasma and faeces on 25 randomly selected farms. Liver samples from animals of local breeds from a slaughter house were collected during the rainy and dry seasons of 1990 and analysed. Soil Fe and Mn were found to be high. Iron contents of all feeds were extremely high and Mn contents were higher than the dietary requirement. A large proportion of feed samples were deficient in Cu and Zinc. There were wide variations in the concentrations of these elements among the soil and feed samples. Blood plasma Fe (P<0.001) and Cu (P<0.01) values differed significantly between the years. Plasma samples collected during 1990 contained lower mean Cu than 1989. The effect of season was statistically significant (P<0.001) for all the trace elements. More than half of the animals were found to have low plasma Cu and Zn during the rainy season. Due to lack of any correlations between soil, pasture and blood plasma it is suggested that analyses of soils and pasture are not reliable for assessing the Fe, Cu and Zn status of grazing cattle in the highlands. Analyses of liver and blood appear to provide better indices.